Angiotensin II receptor blockers and gastrointestinal adverse events of resembling sprue-like enteropathy: a systematic review. (1st June 2019) - Kamal, Ayesha; Fain, Christopher; Park, Angela; Wang, Peiqi; Gonzalez-Velez, Eduardo; Leffler, Daniel A; Hutfless, Susan M
Abstract: Background: Olmesartan, an angiotensin II receptor blocker (ARB), is associated with gastrointestinal symptoms resembling sprue-like enteropathy. Some have proposed that enteropathy may be a class effect rather than olmesartan-specific. We performed a systematic review to identify literature of sprue-like enteropathy for all ARBs. Methods: Case reports, case series and comparative studies of ARBs were searched on PubMed and Embase databases through 21 November 2018 and then assessed. Results: A total of 82 case reports and case series as well as 5 comparative studies, including 248 cases, were selected and analysed. The ARBs listed in the case reports were olmesartan (233 users; 94.0%), telmisartan (5 users; 2.0%), irbesartan (4 users; 1.6%), valsartan (3 users; 1.2%), losartan (2 users; 0.8%) and eprosartan (1 user; 0.4%). The periods between ARB initiation and onset of symptoms ranged from 2 weeks to 13 years. Histologic results were reported in 218 cases, in which 201 cases (92.2%) were villous atrophy and 131 cases (60.1%) were intraepithelial lymphocytosis. Human leucocyte antigen (HLA) testing was performed in 147 patients, among whom 105 (71.4%) had HLA-DQ2 or HLA-DQ8 haplotypes. Celiac-associated antibodies were tested in 169 patients, among whom 167 (98.8%) showed negative results. Gluten exclusion from the diet failed to relieve symptoms of enteropathy in 127 (97.7%) of 130 patients with information. Complete remission of symptoms after discontinuation of ARB was reported in 233 (97.4%) of the 239 patients with information. Seven cases (2.8%) reported recurrence of symptoms after restarting olmesartan; rechallenge was not reported for the non-olmesartan ARBs. The retrospective studies conducted worldwide had inconsistent study designs (e.g. differences in periods of study and case definition) and findings. Conclusions: Although enteropathy is rare, clinicians should remain vigilant of this potential adverse event even years after medication initiation.